A Comparative Study of Using Gi And Co-Op Co-Op Learning Models in Teaching Reading Comprehension of Report Text At The Eleventh Grade Students of Smk Negeri 1 Lumut - Aprida Irmayana; Lollo Rosa Lubis; Taufik Nasution; Dedy Anrio Manalu (National Conference on Language, Education, and Technology Proceeding, 2023)
The purposes of this research was compare the effect of using GI and Co-op Co-op learningmodels in teaching reading comprehension of report text at the eleventh grade TKJ students ofSMK Negeri 1 Lumut. The population of this research consist of 71 students. The sample consistof 33 students taught teaching reading comprehension of report text by using GI learning modeland 38 students were taught teaching reading comprehension of report text by Co-op Co-oplearning model. The researcher used total sampling technique to get the sample. The data wasgotten by giving the test included 25 questions of multiple choices. The result of the researchshowed 1) There is any significant effect of using GI learning model in teaching readingcomprehension of report text and the score N-Gain is 13.887 (low category), 2) There is anysignificant effect of using Co-op Co-op learning model in teaching reading comprehension ofreport text and the score N-Gain is 7.755 (low category),and 3) GI is better than Co-op Co-oplearning model at the eleventh grade TKJ students of SMK Negeri 1 Lumut because the score N-Gain of GI is more than score N-Gain of Co-op Co-op learning model.